An annotated checklist and key to Eugenia (Myrtaceae) from Congo (Brazzaville) - Byng, James W.; Snow, Neil (Phytotaxa, 2018)
We present an annotated checklist of the eight known Eugenia species from Congo (Brazzaville) with information on their distribution, ecology and consulted specimens. Four lectotypes are designated here for species occurring in the country.